ANALYSIS OF CONSTRUCTIVE LOAD CARGO CARDS FOR THE ESTABLISHMENT OF DIRECT STRESS-DEFORMED STATE (Transport systems and technologies, 2018)
In the article presents the features and results of conducted researches on the defini-tion of constructive components of freight wagons for creating a directional stress-strain state (based on the principle of previous stresses). On the basis of the analysis of opera-tional damage, constructive feasibility and technological capabilities, the place of the previous stresses is potentially grounded and systematized in the form of a structural-decomposition scheme. The feasibility and methods of realization of the directed stress-deformed state for car designs are scientifically substantiated. The corresponding results are theoretically illustrated on the example of a tank-wagon, the feasibility of the pro-posed scientific approach for designing the directional stress-strain state of freight cars has been confirmed.
Keywords: mechanical transport, cargo carriage, aiming mode of deformation, load-bearing systems, prestressed components.